A review of the eating disorders literature with reference to dentistry. (2nd July 2021) - Waylen, Andrea
Abstract : Eating disorders are severe psychiatric illnesses associated with physical and psychological morbidity and mortality. In the UK, around 1 in 9 people are directly affected. Oral healthcare professionals may be among the first to observe the signs and symptoms of an eating disorder because of the recognizable and consistent links with oral pathology and it is important that they are sufficiently informed about the condition, and feel confident in raising it with patients and/or their families. CPD/Clinical Relevance: Oral healthcare professionals may be among the first to suspect that a patient has an eating disorder: they can play a role in diagnosis and appropriate referral, as well as providing appropriate oral healthcare advice.